2019
DOI: 10.4028/www.scientific.net/msf.966.263
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Room-Temperature Ferromagnetism in Superconducting Pr<sub>2-</sub><i><sub>x</sub></i>Ce<i><sub>x</sub></i>CuO<sub>4</sub> Nanoparticles

Abstract: Recently, the so-called room-temperature ferromagnetism in any nanoparticles has been studied intensively. It is well known that the properties of ferromagnetism and superconductivity are contradictory in a superconducting high-Tc cuprate. The existence of ferromagnetism in the nanoparticles has been suggested to occur on the surface. This magnetism has been expected to come from defects inducing magnetic moments on oxygen vacancies at the surface of the nanoparticles. This work is to observe magnetism in nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…M. A. Baqiya, et al [15] reported that there is a magnetic transition from weak ferromagnetic to paramagnetic behavior after the reduction annealing in argon. An enhancement of ferromagnetism was also observed at room temperature in the optimally reduced PCCO nanoparticles [16]. This confirms the effect of oxygen vacancy on the magnetic properties of the PCCO nanocrystals.…”
Section: Introductionsupporting
confidence: 77%
“…M. A. Baqiya, et al [15] reported that there is a magnetic transition from weak ferromagnetic to paramagnetic behavior after the reduction annealing in argon. An enhancement of ferromagnetism was also observed at room temperature in the optimally reduced PCCO nanoparticles [16]. This confirms the effect of oxygen vacancy on the magnetic properties of the PCCO nanocrystals.…”
Section: Introductionsupporting
confidence: 77%
“…The search of the high-T c superconductors (HTS) and their behavior opens a new hidden promising property. The socalled apical oxygen is known to be responsible for presenting magnetic behavior, namely, weak ferromagnetic features at room temperature [1]. By means the tetravalent ion doping, a crystalline defect may appear at the apical site and/or at the in-plane oxygen site exhibiting a dominant paramagnetic behavior with a minor weak ferromagnetic feature [2].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is found that the defect recovery on the T'-type structure can be strongly reduce the vacancy at the surface of the nanoparticles [6] in contrast to the full annealing oxygen reduction at vacuum atmosphere [1,2]. This may be related to the number of vacancies recovered and/or created in the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%